MODEL DAN STRATEGI SISWA KELAS II SEKOLAH DASAR DALAM MENYELESAIKAN MASALAH KONTEKSTUAL PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTIK (PMR) - SETIANINGSIH, RINI (Pendidikan Dasar, 2009)
Abstract,This study investigated how grade 2 children learn mathematical concepts using realistic approach. A contextual problem involving multiplication was given to the students. Then, the researcher analysed the students’ strategies in solving such a contextual problem. A fullday school (SD Al Hikmah) was used as the setting of the research, and involved 32 students of grade 2. The children’s self-developed models were assessed through students’work on the student activity sheet, and also through observing the teaching and learning process. An analysis of performance, misconceptions and errors made by the students was achieved through an in-depth analysis of group work. The results suggested that the majority of students were able to solve the contextual problem, employed various models and strategy, while two groups of students engaged in formal method.